Fostering a culture of equity, diversity, and inclusion in the Canadian agricultural economics profession. (8th December 2020) - Yiridoe, Emmanuel K.
Abstract: The Canadian agricultural economics profession, like much of society, is faced with the important challenge of how to effectively achieve aspirational goals of equity, diversity, and inclusion (EDI). I argue that the Canadian agricultural economics society (CAES) will benefit from integrating EDI into our core mission and key activities. I focus on a select set of issues that I believe will further this effort. Given the critical role of scholarly merit and merit‐based systems and processes in the CAES mandate and activities, I also explore how meritocracy and scholarly merit can be aligned with EDI principles. The paper concludes with suggestions and recommendations for consideration by the CAES. Abstrait: La profession d'agroéconomiste canadien, comme une grande partie de la société, est confrontée au défi important de savoir comment atteindre efficacement les objectifs ambitieux d'équité, de diversité et d'inclusion (EDI). Je soutiens que la Société canadienne d'économie agricole (SCEA) va bénéficier de l'intégration de l'EDI dans notre mission principale et nos activités clés. Je me concentre sur une sélection d'enjeux qui, je crois, contribueront à cet effort. Étant donné le rôle essentiel du mérite scientifique et des systèmes et processus fondés sur le mérite dans le mandat et les activités de la SCEA, j'explore également comment la méritocratie et le mérite scientifique peuvent être harmonisés avec les principes de l'EDI. L'article se termine par des suggestions et des recommandations à considérer par la SCEA.